2021
DOI: 10.3389/fpsyg.2021.701629
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Anxiety and Depression and Related Factors Among Pregnant and Postpartum Chinese Women During the Coronavirus Disease 2019 Pandemic

Abstract: Objective: To identify the prevalence of comorbid anxiety and depression (CAD) and analyze the relationship between CAD and sociodemographic and obstetric-related variables in pregnant and postpartum Chinese women during the COVID-19 pandemic.Methods: Participants were 2,237 pregnant and postpartum women (aged 19–47 years) who visited various medical institutions in China between February 28, 2020, and April 26, 2020. They were asked to complete an online survey assessing the anxiety and depression, obstetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 44 publications
4
16
0
Order By: Relevance
“…Moreover, our findings reported a significant positive correlation between fear of COVID-19 and COVID-19-related anxiety levels, as well as between fear of COVID-19 and perinatal depression levels, as already documented in previous studies ( 73 75 ). Furthermore, our findings documented a significant positive correlation between COVID-19-related anxiety and perinatal depression levels, as already demonstrated in previous studies ( 76 , 77 ). In fact, the fear of contagion and for the health of the child, the difficulty in promptly accessing to health care system due to the COVID-19 restrictive measures, as well as the poor availability in being supported by own partner and/or family members during the hospitalization for the delivery may represent all factors which may have determined increased depressive and anxious symptoms in women during the peripartum period ( 67 , 70 , 72 , 78 ).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, our findings reported a significant positive correlation between fear of COVID-19 and COVID-19-related anxiety levels, as well as between fear of COVID-19 and perinatal depression levels, as already documented in previous studies ( 73 75 ). Furthermore, our findings documented a significant positive correlation between COVID-19-related anxiety and perinatal depression levels, as already demonstrated in previous studies ( 76 , 77 ). In fact, the fear of contagion and for the health of the child, the difficulty in promptly accessing to health care system due to the COVID-19 restrictive measures, as well as the poor availability in being supported by own partner and/or family members during the hospitalization for the delivery may represent all factors which may have determined increased depressive and anxious symptoms in women during the peripartum period ( 67 , 70 , 72 , 78 ).…”
Section: Discussionsupporting
confidence: 91%
“…Although there are no specific data regarding postpartum anxiety in the aforementioned systematic reviews, we observed a higher prevalence of clinically significant symptoms of anxiety (26.6 %) compared to a previous multinational study conducted in several European countries and using the same instrument, with mothers up to 3 months following delivery (10 %; Ceulemans et al, 2021 ). Similarly, prevalence of co-morbid symptoms was higher in postpartum women in our sample (20.3 %) compared to the prevalence reported in earlier investigations with perinatal women during the pandemic ( Luo et al, 2021 – 6.3 %; Sun et al, 2021 – [pregnant only] 18 %). In our multinational sample, higher levels of clinically significant symptoms were observed among postpartum than pregnant women, which may reflect mounting psychological demands experienced by women dealing with changes/restrictions/limited access to their postnatal health care, transitioning to motherhood during a pandemic, worrying about the risk of infection to them and their baby, alongside constraints to daily living associated with the pandemic ( Diamond et al, 2020 ; Gildner and Thayer, 2020 ).…”
Section: Discussionsupporting
confidence: 46%
“…Interestingly, the second most common comorbidity in the present COVID-19 patients was depression and anxiety (51%, Table 1). This is in line with several other studies highlighting the impact of pre-existing mental disorders and increased probability of developing COVID-19 [40][41][42].…”
Section: Plos Onesupporting
confidence: 92%